2022
DOI: 10.3389/fenvs.2022.854150
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assessment on Ecological Compensation Based on Water Resources Value Accounting: A Case Study of Water Source Area of the Middle Route of South-To-North Water Transfer Project in China

Abstract: As an economic means to adjust the contradiction between ecology and development, ecological compensation plays an important role in promoting the good operation of interbasin water transfer projects and the sustainable development of regional economy. The accounting of ecological compensation is the key and difficult point of ecological compensation as well as the basis of ecological compensation policy and practice. Watershed ecological compensation based on water resources value accounting is an early explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Second, modern trends in environmental economics and management have been identified: 1) a positive ten-year trend in the Environmental Performance Index and 2) high volatility of total natural resource rents. Because of this, in contrast to Chen et al (2022), Congjuan et al (2022), Popkova (2022), Robinson et al (2022), andWang et al (2022), substantiated that the COVID-19 pandemic did not have a critical impact on the environment due to ecological AI economics and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, modern trends in environmental economics and management have been identified: 1) a positive ten-year trend in the Environmental Performance Index and 2) high volatility of total natural resource rents. Because of this, in contrast to Chen et al (2022), Congjuan et al (2022), Popkova (2022), Robinson et al (2022), andWang et al (2022), substantiated that the COVID-19 pandemic did not have a critical impact on the environment due to ecological AI economics and management.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has shifted priorities from environmental protection to social programs and measures to stimulate economic growth (Almars et al, 2022;Balakesava Reddy et al, 2022;Lim and Abdul Ghani, 2022;Liu et al, 2022;Soomro et al, 2022). The problem is that insufficient attention and lack of funding threaten an environmental crisis, which implies the high relevance of studying as well as finding ways to prevent the latter today (Chen et al, 2022;Congjuan et al, 2022;Popkova, 2022;Robinson et al, 2022;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, for the first time since 1997, the whole channel of YDR was connected with water . This provided a good opportunity to investigate the chemical characteristics of a river transformed from dry-up to continuous . Based on noticed above, this study aims to clarify the water chemistry characteristics of the YDR and evaluate the water quality and health risks of the river water.…”
Section: Introductionmentioning
confidence: 99%
“…However, EC mainly relies on government financial transfer, accompanied by many adverse effects, including insufficient funding sources, ineffective coordination, and poor outcomes in sustainability and equality (Chen et al, 2022). To resolve these problems, scholars have made a series of studies around the coordination of different stakeholders, especially governmental regulation of eco-compensation (Gao, et al, 2019;Jiang et al, 2019;Fang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is effective in resolving this type of problem and has been widely used in influence analysis (Chen et al, 2022). Elzain et al (2022) compared three machine-learning algorithms, and found that the random forest (RF) method performed the most effectively and reliably.…”
Section: Introductionmentioning
confidence: 99%